(untitled) (Mediscope, 2015)
The objective of the prospective randomized controlled comparative study to explore about the role of education in the treatment of irritable bowel syndrome (IBS), a chronic continuous or remittent gastrointestinal illness characterized by frequent unexplained symptoms that include abdominal pain, bloating and bowel disturbance. The patients who fulfilled the set criteria of this study and had normal physical examination were considered to undergo screening investigations (Hb%, TC, DC, ESR, blood glucose, serum TSH, stool for R/M/E and short colonoscopy or double contrast barium enema) to exclude any organic disease. In order to administer the same pharmacological treatment only diarrhea predominant patients without any organic disease were recruited for the present study. The number of recruited patients was 80. Of them, 40 patients were given only pharmacological management with Mebeverine Hydrochloride 135 mg thrice daily half an hour before meal and Amitryptyline 10 mg at night for 6 months, and the other 40 patients were given education by a structured and planned educational class for 1 hr in addition to the same pharmacological treatment. In both groups, changes of symptoms and quality of life of the patients were assessed by using a valid IBS related quality of life (IBS-QOL) instrument. The results showed that significant improvement occurred in both the groups of patients at 1 month and 6 months in respect to their baseline IBS-QOL score. But the improvement was not significantly higher in the group with education in comparison to the group without education. Therefore, it can be concluded that the educational class had no extra impact on drug treatment protocol for IBS used in the present study. Mediscope Vol. 2, No. 2: July 2015, Pages 22-27